Urban Digital Transformation in Jakarta: The Role of Citizen Trust and Digital Attitudes - Melisa Kresentia Sarumaha; Yokie Radnan Kristiyono (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
Digital transformation has significantly reshaped modern urban life, influencing governance, social dynamics, and economic activities. In Jakarta, Indonesia, strategic initiatives such as the JAKI super app, Jakarta Future City Hub, and widespread public Wi-Fi access have accelerated this transformation. Central to its success is the trust citizens place in both government and technology. This study examines the impact of trust in government and trust in technology on Digital Attitudes, with Performance Expectancy and Perceived Risk serving as mediating variables, and Traditional Media and Social Media Acting as moderating variables. Utilising a quantitative approach and Partial Least Squares Structural Equation Modelling (PLS-SEM), the sample in this study consisted of 160 residents of Jakarta who were undergoing digital transformation. Findings reveal that trust in technology significantly influences Digital Attitudes, while trust in government does not. Furthermore, neither mediators nor moderators showed significant effects. These results underscore the importance of technological reliability in shaping public digital engagement and suggest that trust in technology may outweigh institutional trust in driving digital adoption.